Inovasi Limbah Tanaman Sebagai Bahan Baku Sun Protection Factor (SPF) - Berlianna Nur Afiddah; Larasati Fauziah Yakub; Neng Feri Fajarwati; Nia Yuniarsih Yuniarsih (Syntax Idea, 2022)
Garbage is often a problem for people's lives, but if you apply the 3R system it can minimize the buildup, from the 3R system, if it is implemented, it will produce a product. Examples of products that can be produced are sunscreen cosmetic products or Sun Protect Factor (SPF). The negative impact of sunlight that can affect the damage to the skin's epidermis is UV-A and UV-B rays, where these effects can be overcome by giving Sun Protection Factor (SPF). The basic ingredients of Sun Protection Factor (SPF) are useful for protecting human skin health from the negative effects of solar radiation. Herbal plant waste can actually be used as a Sun Protection Factor (SPF) including onion peel (Allium Cepa L), lime peel (Citrus Aurantifolia), corn cobs (Zea Mays L.), banana peel and mangosteen peel (Garcinia). cambogia L.) Onion skin contains phenolic compounds that have a Sun Protection Factor (SPF) value of 11.44 to 31.80. Lime peel contains phenolic compounds, flavonoids and tannins which have a Sun Protection Factor (SPF) value of 4.4; 9.2 to 40.15. Corn cobs contain phenolic compounds that have Sun Protection Factor (SPF) values of 2 to 7. Banana peels contain phenylpropanoid acid compounds, lignins, tannins, coumarins, flavonoids and iso-flavonoids with Sun Protection Factor (SPF) values of 13. ,72 and the mangosteen rind contains flavonoid, phenol, quinone and tannin compounds with a Sun Protection Factor (SPF) value of 29,008. Therefore, the three herbal plant wastes can be used as Sun Protection Factor (SPF) and can reduce waste in the community.